CoRad-19 – Modular Digital Teaching during the SARS-CoV-2 Pandemic - Brendlin, Andreas Stefan; Molwitz, Isabel; Oechtering, Thekla Helene; Barkhausen, Jörg; Frydrychowicz, Alex; Sulkowski, Tanja; Balks, Maren Friederike; Buchholz, Michael; Lohwasser, Stefan; Völker, Martin; Goldschmidt, Olaf; Johenning, Anja; Schlender, Sabine; Paulus, Christian; Antoch, Gerald; Dettmer, Sabine; Baeßler, Bettina; Maintz, David; Pinto dos Santos, Daniel; Vogl, Thomas J.; Hattingen, Elke; Stoevesandt, Dietrich; Reinartz, Sebastian; Storz, Corinna; Müller-Peltzer, Katharina; Bamberg, Fabian; Rengier, Fabian; Weis, Meike; Frisch, Anne; Hansen, Nienke Lynn; Kolb, Manuel; Maurer, Michael; Nikolaou, Konstantin; Afat, Saif; Othman, Ahmed E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Purpose During the SARS-CoV-2 pandemic, higher education worldwide had to switch to digital formats. The purpose of this study was to evaluate CoRad-19, a digital teaching tool created by the German Radiological Society for medical students during the COVID-19 pandemic.Materials and Methods A total of 13 German-speaking universities implemented CoRad-19 in their curriculum and partially or completely replaced their classes with the online courses. Previous experience and contact with radiology and the participantsʼ opinions regarding the medium of e-learning were surveyed using a custom questionnaire. The subjective level of knowledge regarding the individual modules was also surveyed before and after participation to measure learning effects. The data of 994 medical students from the participating sites were analyzed and compared intraindividually using the Friedman test.Results From 4/1/2020–10/1/2020, 451 complete data sets from a total of 994 surveys were included. E-learning was rated “very useful” both before and after course participation (4 [IQR 3–4], p = 0.527, r = 0.16). E-learning as a method was also rated as a “very good” medium both before and after participation (4 [IQR 3–4], p = 0.414, r = 0.17). After participation, participants rated radiology as particularly suitable for digital teaching (before: 3 [IQR 3–4] vs. after 4 [IQR 3–4], p = 0.005, r = 0.6). Significant learning gains were measurable in all course modules (p ≤ 0.009). Post-hoc analysis showed interest in radiology to increase significantly after course participation (p = 0.02).Conclusion In the representative survey, significant learning effects were observed in all course modules. In addition, it should be particularly emphasized that the studentsʼ interest in radiology was increased by course participation. Thus, the German Radiological Society provided significant support to German-speaking medical faculties with respect to maintaining excellent education using CoRad-19.Key Point:Citation FormatZiel Während der SARS-CoV-2-Pandemie musste die Hochschullehre weltweit auf digitale Formate umstellen. In dieser Studie sollte CoRad-19, ein im Rahmen der COVID-19-Pandemie erstelltes digitales Lehrangebot der Deutschen Röntgengesellschaft (DRG) für Medizinstudierende, evaluiert werden.Material und Methoden Insgesamt 13 deutschsprachige Hochschulstandorte haben CoRad-19 in ihr Curriculum implementiert sowie ihre Lehrangebote teilweise oder sogar vollständig durch die Online-Kurse ersetzt. Mithilfe eines eigens entworfenen Fragebogens wurden Vorerfahrungen in und bisherige Kontakte zur Radiologie erfragt sowie die Meinung der Teilnehmenden gegenüber dem Medium E-Learning erhoben. Als Maßstab für den Lernerfolg wurde der subjektive Kenntnisstand bezüglich der einzelnen Module jeweils vor und nach der Teilnahme erhoben. Die Angaben 994 Medizinstudierender aus den beteiligten Standorten wurden analysiert und mittels Friedman-Test intraindividuell verglichen.Ergebnisse Vom 01.04.2020–01.10.2020 wurden aus insgesamt 994 Erhebungen 451 vollständige Datensätze inkludiert. E-Learning wurde sowohl vor als auch nach der Teilnahme an den Kursen als „sehr sinnvoll“ eingeschätzt (4 [IQR 3–4], p = 0,527, r = 0,16). Auch E-Learning als Methode wurde sowohl vor als auch nach der Teilnahme als „sehr gutes“ Medium bewertet (4 [IQR 3–4], p = 0,414, r = 0,17). Nach Teilnahme an den Kursen schätzten die Teilnehmenden die Radiologie als besonders geeignet für digitale Lehre ein (vorher: 3 [IQR 3–4] vs. nachher 4 [IQR 3–4], p = 0,005, r = 0,6). In allen Kursmodulen waren signifikante Lernerfolge messbar (p ≤ 0,009). Eine Post-hoc-Analyse zeigte, dass das Interesse an der Radiologie nach Teilnahme an den Kursen signifikant zunahm (p = 0,02).Schlussfolgerungen In der repräsentativen Umfrage wurden signifikante Lerneffekte in allen Kursmodulen beobachtet. Zudem ist besonders hervorzuheben, dass das Interesse der Studierenden an der Radiologie durch die Kursteilnahme gesteigert werden konnte. Die DRG konnte den deutschsprachigen medizinischen Fakultäten durch CoRad-19 also wichtige Unterstützung bei der Aufrechterhaltung exzellenter Lehre bieten.Kernaussage:Zitierweise
Keywords: radiology; reaching; education; COVID-19; E-Learning